Distribution, prevalence and intensity of moose nose bot fly (Cephenemyia ulrichii) larvae in moose (Alces alces) from Norway - Rolandsen, Christer Moe; Madslien, Knut Ivar Engesæter; Ytrehus, Bjørnar; Hamnes, Inger Sofie; Solberg, Erling Johan; Mysterud, Atle; Vikøren, Turid; Våge, Jørn; Hanssen, Oddvar; Miller, Andrea (International Journal for Parasitology: Parasites and Wildlife, 2021)
High host density combined with climate change may lead to invasion of harmful parasites in cervid (host) populations. Bot flies (Diptera: Oestridae) are a group of ectoparasites that may have strong impact on their hosts, but data on the current distribution, prevalence and intensity of the moose nose bot fly (Cephenemyia ulrichii) in Scandinavia are lacking. We estimated prevalence and intensity of nose bot fly larvae in 30 moose from southern and 79 moose from central Norway. All larvae detected were identified as the moose nose bot fly. We found surprisingly high prevalence in these areas, which are up to 1300 km south-southwest of the first published location in Norway and west of the distribution in Sweden. Prevalence (0.44–1.00) was higher in areas with higher moose density. Parasite intensity in hunter killed moose was higher in central Norway (mean 5.7) than southern Norway (mean 2.9), and in both regions higher in calves and yearlings than adults. Fallen moose had higher parasite intensity (mean 9.8) compared to hunter killed moose in the subsample from central Norway, suggesting a link to host condition or behavior. Our study provides evidence of parasite range expansion, and establishing monitoring appears urgent to better understand impact on host populations.